Speech Acts in Surah Al-Maun and Their Relevance to the Muhammadiyah Social Movement - Hasani, Nurfadila; Borut, Ismail; Bugis, Halima; Ratau, Asria; Umar, Munazar (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study applied speech act theory to analyze Surah Al-Ma'un, the 107th chapter of the Qur'an, to understand how its verses function to convey powerful moral and social messages. The research utilized a qualitative descriptive approach with a focus on pragmatic analysis, drawing upon J.L. Austin and John Searle's Speech Act Theory. Data sources included the original Arabic text of Surah Al-Ma'un, along with reliable English translations and tafsir literature. The analysis categorized the different types of speech acts found in the surah, including assertive, directive, expressive, and commissive functions, and explored their roles in communicating ethical and social meanings.The findings revealed that the Qur'anic language in Surah Al-Ma'un is not merely informative but also transformative, encouraging reflection, emotional response, and real-life action. The verses were found to criticize disbelief, hypocrisy in worship, and the neglect of social duties towards the poor and orphaned. This study also contextualized these findings within the Muhammadiyah movement, demonstrating how the Surah's messages have been translated into practical social actions such as the establishment of orphanages, zakat institutions, schools, and health clinics. The research concluded that Surah Al-Ma'un provides a blueprint for ethical and social action in Muslim communities, highlighting the dynamic role of Qur'anic language in promoting active faith and social justice.